A study on internal customer satisfaction of Samsung SDI (M) - Zakaria, Zulhakim (2001)
There is no doubt that internal customer satisfaction is an important factor influencing one’s job performance. This paper analyses this issues on employees of Samsung SDI (M), which involve in manufacturing color picture tube, color display tube and mount gun. The employees are chosen among the technician levels. The study shows that generally the employees are satisfied with the internal service provided. Nevertheless, there still some matter that needs to be improving in order to enhance the satisfaction of the employees, such as on sports facilities and management system. This is based on the research conducted where majorities of the respondents voice out their dissatisfaction towards these two matters. Samsung SDI (M) has to be more seriously about these matters and try to choose suitable solutions to overcome the problems. The employees are the skeletons of the organization and the organization need to satisfied their needs and wants. By this way, they can work more effectively and efficient.